(untitled) (Research, Society and Development, 2021)
Mining is one of the sectors responsible for land use and occupation of the Brazilian territory, it has been essential for the country’s economic growth. The main growth in the North Region, in the state of Pará, is located in Serra dos Carajás, where one of the largest deposits of pure iron ore in the world is located. That is why it is important to analyze a future socio-environmental impact in the event of a collapse of the dam that receives the waste from iron production, through the flow of tailings within a radius of 50 km from the affected area, using as a basis the images of the ALOS sensor PALSAR, with a resolution of 12.5 meters. Upon analysis, it appears that in case of rupture, the affected area will first be Parauapebas due to its location, right after the cities of Marabá and the Canaã region, according to the types of elevation shown on the map, causing environmental, social and even such effects that can be irreversible and difficult to manage. Thus, to mitigate and prevent damage, legislation must be strengthened through better governance practices, structured monitoring programs, strictness in environmental laws, inspections by competent environmental agencies for dam activities and the release of environmental licenses.